Intraoperative Awareness Among Patients Following General Anaesthesia - A Descriptive, Cross - sectional study. - Raj Kunwar, Bhuban; Shah, Aashish (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Operative awareness with recall refers to recalling of the intra operative events in the post-operative period by the patients which may have significant psychological and legal implications. Bispectral index (BIS) analysis is a processed EEG that can be used to monitor the depth of anaesthesia, titrate the dose of anaesthetic agents and hence prevent intraoperative awareness. Methods: It is a prospective, cross-sectional, observational study, where total of 103 cases operated under general anaesthesia were included. BIS score was monitored intraoperatively at various points of time during the surgery and Modified Brice questionnaires was used in post-operative to illicit intraoperative awareness. Results: The maximum and minimum BIS score was 97.46 ± 0.84 before induction and 50.20 ± 7.43, 30 minutes after intubation. None of the patients remembered anything between going to sleep and waking up indicating there was no incidence of awareness. However, 55.4% remembered “seeing the operating room before going to sleep”, 71.8% remembered “hearing voices’’ first thing after waking up and 59.3% were worried about pain in the post-operative period. Conclusion: There were no incidence of intraoperative awareness among the patients during surgery under general anaesthesia.